trade and market in the governorate of snuff Jaen Bracamoros in the first half of the eighteenth century - Ernesto Morales, Carlos (2013)
With the Bourbon reformism Luya Saña and Chachapoyas were bought important for the development of the agriculture of tobacco. Jaén’s government of Bracamoros with the other regions they formed a territorial emerging space that got connected economic and socially to the viceroyalty of the Peru, included James of Chile. The interchange between the regions should have been crucial for the population’s cost-reducing maintenance. The resource that generated bigger quantity of income at the region was the exportation of tobacco which was commercialized at the Kings’s city. Saña’s province acquired Jaén’s tobacco for its commercialization to the kings’s city, Blind Fury also gave resources to Jaén’s province articulating both regions.